Early medieval Hum and Bosnia, c.450-1200 - Džino, Danijel, author.
1 online resource.
Keywords: "This book explores social transformations which led to the establishment of medieval Hum (future Herzegovina) and Bosnia in the period from ca. 450 to 1200 AD using the available written and material sources. It follows social and political developments in these historical regions from the last centuries of Late Antiquity, through the social collapse of the seventh and eighth centuries, and into their new medieval beginnings in the ninth. Fragmentary and problematic sources from this period were, in the past, often used to justify modern political claims to these contested territories and incorporate them into the 'national biographies' of the Croats, Serbs and Bosniaks (Bosnian Muslims), or to support the 'Yugoslavizing' and other ideological discourses. The book goes beyond ideological and national mythologemes of the past in order to provide a new historical narrative that brings more light to this region placed on the frontiers of both the medieval West and the Byzantine empire. It provides a new views of the period between ca. 450 and 1200 for the parts of Western Balkans and Eastern Adriatic, brings the most recent local historical and archaeological research to the Anglophone readership, and contributes to the scholarship of the late antique and early medieval Mediterranean with study of very poorly known area. The book is intended for academic audience interested in history and archaeology of the Late Antiquity and early Middle Ages, but also to all those interested in general history of Herzegovina, Bosnia, Dalmatia and the Balkans"--